Identification of a microRNA signature associated with progression of leukoplakia to oral carcinoma - Cervigne, Nilva K. [UNESP]; Reis, Patricia P.; Machado, Jerry; Sadikovic, Bekim; Bradley, Grace; Naranjo Galloni, Natalie; Pintilie, Melania; Jurisica, Igor; Perez-Ordonez, Bayardo; Gilbert, Ralph; Gullane, Patrick; Irish, Jonathan; et al. (Oxford University Press, 2009)
MicroRNAs (miRs) are non-coding RNA molecules involved in cancer initiation and progression. Deregulated miR expression has been implicated in cancer; however, there are no studies implicating an miR signature associated with progression in oral squamous cell carcinoma (OSCC). Although OSCC may develop from oral leukoplakia, clinical and histological assessments have limited prognostic value in predicting which leukoplakic lesions will progress. Our aim was to quantify miR expression changes in leukoplakia and same-site OSCC and to identify an miR signature associated with progression. We examined miR expression changes in 43 sequential progressive samples from 12 patients and four non-progressive leukoplakias from four different patients, using TaqMan Low Density Arrays. The findings were validated using quantitative RT-PCR in an independent cohort of 52 progressive dysplasias and OSCCs, and five non-progressive dysplasias. Global miR expression profiles distinguished progressive leukoplakia/OSCC from non-progressive leukoplakias/normal tissues. One hundred and nine miRs were highly expressed exclusively in progressive leukoplakia and invasive OSCC. miR-21, miR-181b and miR-345 expressions were consistently increased and associated with increases in lesion severity during progression. Over-expression of miR-21, miR-181b and miR-345 may play an important role in malignant transformation. Our study provides the first evidence of an miR signature potentially useful for identifying leukoplakias at risk of malignant transformation.